An unprecedented nanocage-like and heterometallic [MoIV3O4]-polyoxomolybdate hybrid. Issue 10 (7th February 2018) - Xu, Xian; Luo, Ben-long; Wang, Lu-Lu; Xu, Li
Abstract : A general synthetic route toward [MoIV3O4 ]-POMs is established to yield the first Mo 4+ –Mo 5+ –Mo 6+ nanocage cluster, Na[(MoIV3O4 )4 MoV4MoVI3O27 (OH)Py12 ] (1 ) and the first heterometallic hybrid, H2 [(MoIV3O4 )MoVI10Zn(PO4 )4 (OH)2 O27 py3 ] (2 ) (Mo 4+, pink; Mo 5+, green; Mo 6+, black green; P, yellow; Zn, aqua. Abstract : The solvothermal oxidation of [Mo3 O2 (O2 CCH3 )6 (H2 O)3 ]·ZnCl4 has been established as a general route toward [Mo 4+ 3 O4 ]-incorporated polyoxomolybdates (Mo IV -POMs). Two unprecedented family members: the first Mo 4+ –Mo 5+ –Mo 6+ nanocage cluster, Na[MoIV12MoV4MoVI3O43 (OH)Py12 ]·11H2 O (1 ) and the first heterometallic hybrid, [MoIV3MoVI10Zn(PO4 )4 (OH)2 O31 py3 ]·2(C5 H6 N)·3(C5 H5 N)·2H2 O (2 ) have been prepared and characterized by X-ray crystallography, elemental and DFT theoretical analyses, XPS, mass spectroscopy, cyclic voltammetry, and IR spectroscopy.